Ecology and epidemiology of Japanese encephalitis virus in Nepal, and dynamics of infection with the virus in birds and mosquitoes - Karna, Ajit Kumar, author; Bowen, Richard A., advisor; Foy, Brian D., advisor; Blair, Carol D., committee member; Olea-Popelka, Francisco, committee member (Colorado State University. Libraries, 2017)
Japanese encephalitis virus (JEV) infection is common in humans and other animals in Asia, including Nepal. Morbidity and mortality due to JEV infection are higher in children than adults, although all age groups of people are vulnerable to JEV, as the areas suitable for rice paddy farming and reservoir host farming are ecologically excellent sites for virus transmission. Several countries currently practice childhood immunization; however, it is limited mostly to city hospitals and frequently does not reach people in rural areas who need it most. The studies reported here had the overall aim to study the ecology and epidemiology of endemic JEV infection in Nepal. The prevalence of JEV infection in domestic animals is poorly studied at the household scale and is important in assessing the risk of exposure of JEV to humans. Pigs, ducks, and chickens from Rupandehi district of Nepal were tested for antiviral antibody as an index of exposure to JEV, and seroprevalence was characterized for each species at both individual animal and farm level. Additionally, risk factors for JEV exposure to individual species of animal and their farms were assessed. The seroprevalence in pigs, ducks, and chickens was estimated to be 14.7%, 11.8%, and 6.7%, respectively. The farm level seroprevalence of JEV was 31.7%, 31.6%, and 12.8% for farms with pigs, ducks, and chickens, respectively. The major risk factors for JEV infection in these animals were age, locality, practicing household fermentation, farm size, and location of the farm in the household courtyard. However, the risk factors differed by species of animal. The incidence of JEV infection in humans is influenced by humans' beliefs, thoughts, and actions, which guides them to different preventive measures. To better understand the influence of these factors, a knowledge, attitude, and practice survey was conducted among 183 households in the Rupandehi district of Nepal to determine whether prior knowledge, current attitudes, and current practices regarding JE/JEV (response variables) guide people in choosing one or the other practices to prevent infection with JEV (outcome of interest). Participants were asked several open- and close-ended questions, and the data were analyzed using univariable and multivariable approaches. The outcomes of interest to which several response variables were analyzed were (i) mosquito population control (removal of stagnant water from surroundings and use of insecticides) and (ii) prevention of mosquito bite (application of insect repellent and using a bed net). Depending on several aspects of knowledge, attitude, and practices, one or the combination of approaches were found to be associated. Mosquito surveillance for arboviruses is infrequently pursued in Nepal, and the Culex species vectors of human pathogens are poorly characterized. A 13-week mosquito sampling in the Rupandehi district of Nepal was carried out at eight different locations to characterize the diversity of Culex vectors of JEV, estimate their abundance, blood feeding activity, and to evaluate the influence environmental conditions on those variables. Culex tritaeniorhynchus was the most common vector during the course of the study, although 17 additional Culex species were detected. Among environmental factors, temperature and precipitation were either positively or negatively correlated with the abundance of different Culex vectors. A final set of studies had the objective to better understanding the phenomenon of genotype displacement for JEV. Since ducks and Culex quinquefasciatus mosquitoes are prevalent avian hosts and vectors perpetuating JEV transmission in JE endemic areas, experimental evaluation of virus replication in these species was considered to approximate the natural conditions necessary for studying the role of host, vectors and viral fitness in the JEV genotype displacement context. We evaluated viremia in ducklings infected with three genotype I and three genotype III strains of JEV, and did not detect differences in magnitude or duration of viremia among viruses representing displaced and displacing genotypes. Testing the same six viruses in mosquitoes revealed that the median rates of infection, dissemination and transmission were higher in viruses belonging to genotype I than those representing genotype III, and that the extrinsic incubation period was shorter for the genotype I virus strains. These data suggest that the characteristics of JEV infection of mosquitoes but not of ducklings, may play a role in genotype displacement.
Keywords: extrinsic incubation period; Japanese encephalitis virus; vector competence; genotype displacement; seroprevalence; Culex